Development and Characterization of Nanoemulsion Containing Volatile Oil of Matricaria recutita L. - Brenda Alves Lopes; Patrícia Döll Boscardin; Patrícia Mazureki Campos (Brazilian Archives of Biology and Technology, 2023)
Abstract Nanoemulsions (NEs), emulsified systems with diameter between 20 and 500 nm, are promising in cosmetic science due to stability and efficient transportation of lipophilic substances, such as volatile oils, favoring the skin penetration to carry out the biological activity. Volatile oil of Matricaria recutita L. (VOMR) has several therapeutic effects, but the lability of the volatile oils requires appropriate vehiculation in NEs. Besides, the hydrophilic-lipophilic balance (HLB) parameter for VOMR is not described in the literature. Therefore, NEs composed of Span® 80, Tween® 80, PEG-7 glyceryl cocoate, glycerin and water were developed by the high-energy method. The NEs were characterized by organoleptic, physicochemical and morphological evaluations as well as the stability evaluation was conducted at different temperatures for 60 days. The NEs obtained with and without VOMR exhibited translucent aspect, pH of 4.82 and 5.62; average diameter of 104.97 ± 4.03 and 92.32 ± 6.17 nm; polydispersity index of 0.27 ± 0.06 and 0.31 ± 0.04, and zeta potential of -28.37 ± 3.06 and -36.48 ± 6.56 mV, respectively. The encapsulation of VOMR was around 83% into the NE and confirmed by visualization through scanning electron microscopy - field emission gun. The stability study demonstrated that refrigeration is the optimal storage condition because the conservation of the NEs characteristics. As a result, the present study describes for the first time HLB value near 7 for VOMR. Thus, NE with this volatile oil was developed with suitable characteristics, contributing to technology development of phytopharmaceuticals for topical application to the skin.